7681°N En upptäcktsresa vid världens ände - Karami,Mina (Diploma work, 2013)
This is not a traditional industrial design project. Our ”product” is the mediation of our experiences during the spring of 2011, where a fascination for Svalbard and human driving forces plays a central part. The project is also a search; for our profession, for alternative design values and methods - venturing out into the unknown and exploring unbeaten paths of design practice. In March 2011, we travelled to Longyearbyen, the main settlement of Svalbard. Happenstance and fortunate circumstances brought us together with people who for various reasons were staying in Longyearbyen. They let us into their lives and shared parts of their life stories with us. 7681°N has been a search and an exploration driven by curiosity and intuition. Our results are our experiences, our thoughts and reflections, before, during and after our trip, where the people we met on Svalbard play a central role. We have selected abstracts from our journey and from the conversations we had and packaged the experiences in a book. The texts are about seeking and finding your place, about daring to leave the safe and habitual and venture out into something new and unknown. Our goal is to share our experiences - with a desire to inspire and be inspired.